Profile of boys with posterior urethral valves from a tertiary care center in a developing country - Jain, Ashish; Manthan, Mukta; Kumari, Nisha; Singh, Srijan (Indian Journal of Child Health, 2018)
Introduction: Posterior urethral valves (PUVs) are the most common cause of obstructive uropathy in boys. While most patients in developed countries are diagnosed in the antenatal period, our patients often present late which adversely affects their outcome. This retrospective study was aimed to study the clinical profile of boys with PUV at follow-up. Methods: Records of 45 boys  with PUV who were in follow-up for at least 1-year were retrieved between February and December 2015. Age of presentation, signs and symptoms, anthropometry, radiological findings, surgical interventions, and biochemical investigations were recordedin a pre-structured pro forma. The data were later analyzed on an Excel spreadsheet. Results: The mean age at the diagnosis of PUV was 16±2.8 months, and the mean age at enrollment was 70.6±53.5 months. The condition was detected antenatally in 5 (10.9%) subjects only. At the time of data collection, the mean height and weight standard deviation scores were ?1.7 and ?1.5, respectively. Hypertension was present in 29% of patients. 44.5% of subjects had moderate-to-severe malnutrition and 42.2% had short stature. Mean GFR of the subjects was 66.3 ml/min/1.73m². Bilateral hydronephrosis was present on ultrasound in 26 (57.8%) subjects. Mean anteroposterior diameter on ultrasound was 22.1 mm for the right kidney and 20.8 mm for the left kidney. Significant post-void residue was detected in 54.6% of patients. Bilateral reflux was seen in 21.7% of subjects on micturating cystourethrogram. Urodynamic studies were available for 16 patients, and 31.3% had significant post-void residual urine. Detrusor instability was present in 18.8% of subjects. 35.6% of subjects underwent valve fulguration alone as the surgical procedure while 19 (42.2%) had a diversion procedure  (vesicostomy/ureterostomy) along with valve fulguration. Conclusions: Most of the patients with PUV arestill diagnosed postnatally and have significant renal damage at presentation. Urinary diversion procedures are required in almost half of these patients. All these contribute to a poor long-term outcome.